Mandatory retention rules and bank risk - Yuteng Cheng (Bank of Canada, 2023)
This paper studies, theoretically and empirically, the unintended consequences of mandatory retention rules in securitization. The Dodd-Frank Act and the EU Securitisation Regulation both impose a 5% mandatory retention requirement to motivate screening and monitoring. I first propose a novel model showing that while retention strengthens monitoring, it may also encourage banks to shift risk. I then provide empirical evidence supporting this unintended consequence: in the US data, banks shifted toward riskier portfolios after the implementation of the retention rules embedded in Dodd-Frank. Furthermore, the model offers clear, testable predictions about policy and corresponding consequences. In the US data, stricter retention rules caused banks to monitor and shift risk simultaneously. According to the model prediction, such a simultaneous increase occurs only when the retention level is above optimal, which suggests that the current rate of 5% in the US is too high.
Keywords: G21; G28; 330; Financial institutions; Financial system regulation and policies; Credit risk management